SARS-CoV-2 variant-specific differences in inhibiting the effects of the PKR-activated integrated stress response - Christ, Wanda; Klingström, Jonas; Tynell, Janne (Virus research, 2024)
•SARS-CoV-2 triggers the integrated stress response through activation of PKR.•Omicron induces more stress granule formation than Delta or Ancestral SARS-CoV-2.•ISR inhibition negatively affects SARS-CoV-2 replication. The integrated stress response (ISR) is a eukaryotic cell pathway that triggers translational arrest and the formation of stress granules (SGs) in response to various stress signals, including those caused by viral infections. The SARS-CoV-2 nucleocapsid protein has been shown to disrupt SGs, but SARS-CoV-2 interactions with other components of the pathway remains poorly characterized. Here, we show that SARS-CoV-2 infection triggers the ISR through activation of the eIF2α-kinase PKR while inhibiting a variety of downstream effects. In line with previous studies, SG formation was efficiently inhibited and the induced eIF2α phosphorylation only minimally contributed to the translational arrest observed in infected cells. Despite ISR activation and translational arrest, expression of the stress-responsive transcription factors ATF4 and CHOP was not induced in SARS-CoV-2 infected cells. Finally, we found variant-specific differences in the activation of the ISR between ancestral SARS-CoV-2 and the Delta and Omicron BA.1 variants in that Delta infection induced weaker PKR activation while Omicron infection induced higher levels of p-eIF2α, and greatly increased SG formation compared to the other variants. Our results suggest that different SARS-CoV-2 variants can affect normal cell functions differently, which can have an impact on pathogenesis and treatment strategies.